IDENTIFIKASI PENCEMARAN LOGAM BERAT TANAH PERMUKAAN DI SEKITAR PLTU TELUK SIRIH DENGAN METODE SUSEPTIBILITAS MAGNETIK - Manalu, Githa Sortania; Afdal, Afdal (Universitas Andalas, 2025)
Magnetic susceptibility analysis of surface soil around Teluk Sirih Power Plant in Padang city has been conducted. Soil sampling was conducted at 28 points at a depth of 30 cm. The results show that the magnetic susceptibility value of surface soil range from 81.4667×10-8 m3/kg to 934.2133×10-8 m3/kg. The magnetic susceptibility value indicates that the surface soil around the PLTU is moderately to highly polluted, with several points of low pollution. The further from the PLTU, the lower the magnetic susceptibility value, indicating that the pollution comes from emissions from coal combustion at the PLTU. The further from the road, the lower the magnetic susceptibility value, indicating that there are other sources of pollution from vehicle emissions passing through the road. It also found that vegetation affects the level of soil pollution as indicated by the magnetic susceptibility value in the vegetated zone being lower than the magnetic susceptibility value in the non-vegetated zone.